Incidence of urethral stricture in patients with urethral trauma: a 10-year experience in an Indonesian tertiary hospital - Satyagraha, Paksi; Lazuardi, Muhammad Adi Satrio; Budaya, Taufiq Nur (Medical Journal of Indonesia, 2024)
BACKGROUND Urethral injuries are rarely life-threatening but can cause significant morbidity if left untreated. Until now, data on urethral trauma incidence are still limited in Indonesia. This study aimed to report the incidence of traumatic urethral stricture within 10 years of experience in treating urethral trauma. METHODS This retrospective study used a total sampling method for all patients with urethral trauma who came to the emergency department and agreed to undergo radiological evaluation. Patient data were collected from January 2012 to December 2021. All patients were followed up for 3 months after trauma, and the incidence of urethral stricture was analyzed using the chi-square or Fisher's exact tests as an alternative. RESULTS The overall incidence of urethral stricture was 48.4%. Of 122 patients, 82.0% had anterior urethral trauma. Grade III American Association for the Surgery of Trauma (43.4%) was the most common urethral trauma. The cause of urethral trauma was iatrogenic, pelvic fracture urethral injury (PFUI), straddle injury, and penile fracture, contributing in 64.8%, 18.0%, 16.4%, and 0.8% of the cases, respectively. Most patients (70.5%) underwent a cystostomy catheterization procedure as initial treatment. Straddle injury, PFUI, and a higher degree of urethral trauma were significantly associated with urethral stricture formation (p<0.05). CONCLUSIONS Straddle injury, PFUI, and a higher degree of urethral trauma were significantly related to a higher incidence of urethral stricture. Most low-grade and anterior urethral traumas can resolve spontaneously.